Atomistic tight-binding computations of excitonic fine structure splitting in CdSe/ZnSe type-I and ZnSe/CdSe invert type-I core/shell nanocrystals. (1st June 2016) - Sukkabot, Worasak
Abstract: The excitonic fine structure splitting (FSS) in semiconductor core/shell nanocrystals is intrinsically caused by electron-hole exchange interactions. Here, I present the model based on the combination of the atomistic tight-binding theory (TB) and configuration interaction description (CI) that allows determining the band-edge excitonic fine structure. Using this atomistic model, I highlight the operation of the excitonic fine structure splitting by engineering the type of the band alignments and the thickness of the growth shell in CdSe/ZnSe type-I and ZnSe/CdSe invert type-I core/shell nanocrystals, indicating to control the location of the carrier confinement in these nanostructures. To theoretically examine the atomistic behaviors of excitonic fine structure splitting, the single-particle spectra, optical band gaps, ground-state wave function overlaps, ground-state coulomb energies, ground-state exchange energies, dark-bright (DB) excitonic splitting and bright-bright (BB) excitonic splitting are computed. I discover that ZnSe/CdSe invert type-I core/shell nanocrystals provide a sturdily reduced energies of DB and DB excitonic splitting as described by a diminished electron-hole exchange interaction. Besides, the energies of DB and DB excitonic splitting are decreased with the increasing dimensions of the growth shell. This deeper insight is much important for the theoretical understanding and practical control by type of the band alignments and sizes in growth shell with the aim to generate the entanglement of the polarized photon source in the application of the quantum information processing.